Contactless non-destructive imaging of doping density and electrical resistivity of semiconductor Si wafers using lock-in carrierography. (24th October 2018) - Song, Peng; Melnikov, Alexander; Sun, Qiming; Mandelis, Andreas; Liu, Junyan
Abstract: A contactless non-destructive imaging method for spatially resolved dopant concentration, [2.2] N d, and electrical resistivity, ρ, of n - and p -type silicon wafers using lock-in carrierography images at various laser irradiation intensities is presented. Amplitude and phase information from wafer sites with known resistivity was employed to derive a calibration factor for accurate determination of the absolute carrier generation rate. A frequency-domain model based on the nonlinear nature of photocarrier radiometric signals was used to extract dopant density images. Lateral variations in the resistivity of an n -type and a p -type wafer obtained by means of this methodology were found to be in excellent agreement with those obtained with conventional 4-point probe measurements. This all-optical contactless method can be used as a non-destructive tool for doping density and electrical resistivity measurements and their images over large semiconductor areas. N d, ρ and their variances can be measured and mapped for the photovoltaic, micro- and opto-electronic industries including on wafers with oxides or surface treated layers for which contacting electrical measurements are impossible.